Type I Interferon, Induced by Adenovirus or Adenoviral Vector Infection, Regulates the Cytokine Response to Lipopolysaccharide in a Macrophage Type-Specific Manner - Mareike D. Maler; Sophie Zwick; Carsten Kallfass; Peggy Engelhard; Hexin Shi; Laura Hellig; Pang Zhengyang; Annika Hardt; Gernot Zissel; Zsolt Ruzsics; Willi Jahnen-Dechent; Stefan F. Martin; et al. (Karger Publishers, 2024)
Introduction: While TLR ligands derived from microbial flora and pathogens are important activators of the innate immune system, a variety of factors such as intracellular bacteria, viruses, and parasites can induce a state of hyperreactivity, causing a dysregulated and potentially life-threatening cytokine over-response upon TLR ligand exposure. Type I interferon (IFN-αβ) is a central mediator in the induction of hypersensitivity and is strongly expressed in splenic conventional dendritic cells (cDC) and marginal zone macrophages (MZM) when mice are infected with adenovirus. This study investigates the ability of adenoviral infection to influence the activation state of the immune system and underlines the importance of considering this state when planning the treatment of patients. Methods: Infection with adenovirus-based vectors (Ad) or pretreatment with recombinant IFN-β was used as a model to study hypersensitivity to lipopolysaccharide (LPS) in mice, murine macrophages, and human blood samples. The TNF-α, IL-6, IFN-αβ, and IL-10 responses induced by LPS after pretreatment were measured. Mouse knockout models for MARCO, IFN-αβR, CD14, IRF3, and IRF7 were used to probe the mechanisms of the hypersensitive reaction. Results: We show that, similar to TNF-α and IL-6 but not IL-10, the induction of IFN-αβ by LPS increases strongly after Ad infection. This is true both in mice and in human blood samples ex vivo, suggesting that the regulatory mechanisms seen in the mouse are also present in humans. In mice, the scavenger receptor MARCO on IFN-αβ-producing cDC and splenic marginal zone macrophages is important for Ad uptake and subsequent cytokine overproduction by LPS. Interestingly, not all IFN-αβ-pretreated macrophage types exposed to LPS exhibit an enhanced TNF-α and IL-6 response. Pretreated alveolar macrophages and alveolar macrophage-like murine cell lines (MPI cells) show enhanced responses, while bone marrow-derived and peritoneal macrophages show a weaker response. This correlates with the respective absence or presence of the anti-inflammatory IL-10 response in these different macrophage types. In contrast, Ad or IFN-β pretreatment enhances the subsequent induction of IFN-αβ in all macrophage types. IRF3 is dispensable for the LPS-induced IFN-αβ overproduction in infected MPI cells and partly dispensable in infected mice, while IRF7 is required. The expression of the LPS co-receptor CD14 is important but not absolutely required for the elicitation of a TNF-α over-response to LPS in Ad-infected mice. Conclusion: Viral infections or application of virus-based vaccines induces type I interferon and can tip the balance of the innate immune system in the direction of hyperreactivity to a subsequent exposure to TLR ligands. The adenoviral model presented here is one example of how multiple factors, both environmental and genetic, affect the physiological responses to pathogens. Being able to measure the current reactivity state of the immune system would have important benefits for infection-specific therapies and for the prevention of vaccination-elicited adverse effects.